Pengaruh Komitmen Pegawai Sekolah Terhadap Eektivitas Implementasi Total Quality Management (Tqm) di SMKN Se-Kota Cimahi - ., Syukron; Chusnul Kurniatun, Taufani; Bakar, H. Abu (Jurnal ADPEND, 2016)
Total Quality Management (TQM) is trying improvement and increasement the qualityÂ continously all persons. TQM is a inovation in managing a education which make focus in improvingÂ and increasing the quality continously which oriented to customerâsatisfaction. Standard of EducationÂ and The Quality Management System ISO 9001:2008 in The Vacational School is a role and qualityÂ giudance contain minimun criteria and achievement the quality which must be finished school inÂ operating one of education.both of them must finish consistently in order to purpose school canÂ achieve, namely involving and enableness all school society.that thing,the observer is imterested toÂ indentify about âComitment Of School Society About Implementation Effectivity Total QualityÂ Management In SMKN In Cimahiâ.The purpose of obserment id is to know commitment of school society about organisation,toÂ know implementatiom effectivity TQM and to know school society about implementation EffectivityÂ TQM. The method that is used in the observement is the method quantative, that is located in SMKNÂ CIMAHI, by using technic sample random sampling in sample taking. A informant as data source andÂ tecnic data collecting that is used questionnaire and interview. And the usage programme SPSSÂ version 21.0 and Microsoft Excel in data processing.According data processing result Weight Mean Score (WMS) find observernent in schoolÂ society in SMKN CIMAHI in the position EXCELLENT in getting score 4,13 where SMKN 1 HasÂ low score 4,08 and HIGH score SMKN 2 4,37 meanwhile SMKN 3 is 4,31 and the next aboutÂ implementation Effectivity TQM in School Cimahi has WELL generally in rate score 3,97 whichÂ SMKN 1 (4,00) has high score from SMKN 2 (3,97) SMKN 3 (3,91) have low score among the otherÂ school. Meanwhile finding from normality test result that variable data X and Y distribute Normal,Â data processing and data analysis use parametic statistic technic. From variable corelation coefisionÂ test X and Y is gotten 0,710 and test result Signification is gotten value t-hitung 12,488 and t-tabel 1,804and coefision test result detemination is getting 50,5% it means commitment of school society inflenceÂ strongly 50,5% and signification about effectivity implementatiom TQM in SMKN CIMAHI. 49,5% isÂ influenced other factor is included he obcerverment. The conclusion that a need consistent teachersÂ and administration staff as school society to commite about organisation through obedience aboutÂ quality operate the job according the quality guidance.